2016
DOI: 10.1126/science.aaf2669
|View full text |Cite
|
Sign up to set email alerts
|

Autism-associated SHANK3 haploinsufficiency causes I h channelopathy in human neurons

Abstract: Heterozygous SHANK3 mutations are associated with idiopathic autism and Phelan-McDermid syndrome. SHANK3 is a ubiquitously expressed scaffolding protein that is enriched in postsynaptic excitatory synapses. Here we used engineered conditional mutations in human neurons to show that heterozygous and homozygous SHANK3 mutations severely and specifically impair Ih-channels. SHANK3 mutations caused alterations in neuronal morphology and synaptic connectivity; chronic pharmacological blockage of Ih-channels reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
268
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(299 citation statements)
references
References 60 publications
(86 reference statements)
19
268
2
Order By: Relevance
“…Evidence increasingly supports that neurodevelopmental and neuroplastic processes regulating spine and glutamatergic synapses contribute to the pathogenesis of psychiatric conditions including autism, schizophrenia and major affective disorders [2,3,4,40,41,42,43]. In line with this, several PCP proteins contributing to these processes have been implicated in psychiatric pathophysiology.…”
Section: Discussionmentioning
confidence: 72%
“…Evidence increasingly supports that neurodevelopmental and neuroplastic processes regulating spine and glutamatergic synapses contribute to the pathogenesis of psychiatric conditions including autism, schizophrenia and major affective disorders [2,3,4,40,41,42,43]. In line with this, several PCP proteins contributing to these processes have been implicated in psychiatric pathophysiology.…”
Section: Discussionmentioning
confidence: 72%
“…HCN channels are found in the cardiac sinoatrial node and throughout the nervous system, where they open in response to membrane hyperpolarization and generate a depolarizing current responsible for rhythmic firing (1). HCN channel mutations and mistrafficking have been associated with several disorders, including sinus bradycardia, epilepsy, and autism (3,4).…”
mentioning
confidence: 99%
“…S5A,B; cf. Yi et al 2016). We found that, in human ESC (hESC)-induced neurons, expression of shRNA-PalGFP-IRES-GFP-hBRaf(V600E) and shRNA-PalGFP-IRES-GFP-hBRaf (K499E) increased the levels of phosphorylated p42/44 MAPK, whereas expression of shRNA-PalGFP-IRES-GFP-hBRaf(G469E) and shRNA-PalGFP-IRES-GFP-hBRaf (K482M) decreased the levels of phosphorylated p42/44 MAPK (Supplemental Fig.…”
Section: Braf Signals In Neurons Of Various Speciesmentioning
confidence: 99%
“…Human neurons were prepared from H1 ESCs and GM-1 cells using protocols modified from previous studies (Pang et al 2011;Williams et al 2014;Du et al 2015;Yi et al 2016). Briefly, to prepare hESC-induced neurons, H1 ESCs were cultured feeder-free on Corning Matrigel membrane matrix-coated (Thermo Fisher) plates and fed daily with mTeSR1 medium (Stem Cell Technologies).…”
Section: Human Neuron Preparationmentioning
confidence: 99%